1998
DOI: 10.1111/j.1540-8167.1998.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Ventricular Repolarization in Left Ventricular Hypertrophy: Influence of Afterload and Dofetilide

Abstract: Epicardial APD dispersion decreases in hypertrophied hearts following an increase in afterload, and this response is mediated in part by the absence of afterload-induced shortening of the APD. This effect may be due in part to altered responses of the delayed rectifying current to cardiac loading conditions in the setting of cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…15 In another study by Bauer et al, 7 a limited section of the LV was investigated by tridimensional recordings. In the study by Gillis et al, 8 only epicardial MAP recordings were analyzed. The present study leaves little doubt that significant spatial DR can develop between contiguous ventricular sites in the in vivo canine heart and can provide the primary substrate for functional conduction block and reentrant tachyarrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In another study by Bauer et al, 7 a limited section of the LV was investigated by tridimensional recordings. In the study by Gillis et al, 8 only epicardial MAP recordings were analyzed. The present study leaves little doubt that significant spatial DR can develop between contiguous ventricular sites in the in vivo canine heart and can provide the primary substrate for functional conduction block and reentrant tachyarrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several studies have questioned whether marked spatial dispersion of ventricular repolarization is detectable in vivo [5][6][7] and whether class III antiarrhythmic agents result in an increased DR in the hypertrophied heart. 8 The present study was conducted to investigate if the hypertrophied heart is associated with increased spatial DR in vivo and an increased susceptibility to proarrhythmic effects of class III antiarrhythmic agents. For this purpose, we investigated a known model of ventricular hypertrophy 9 in which dogs with chronic atrioventricular (AV) block develop ventricular hypertrophy secondary to chronic volume overload.…”
mentioning
confidence: 99%
“…13 Dofetilide reduced dispersion of repolarization in normal animals 38 but had no effect on dispersion of repolarization in a canine myocardial infarction model 39 or in a rabbit model of left ventricular hypertrophy. 40 In patients with stable angina or ventricular tachycardia, dispersion of repolarization was not affected by dofetilide. 16,17 Pharmacokinetics Dofetilide is well absorbed after oral administration, with an absolute bioavailability of Ͼ90%.…”
Section: Effects Of Dofetilide On Arrhythmias In Animal Modelsmentioning
confidence: 99%
“…It has been shown that long-term administration of IGF-I regulates the expression of the K ϩ channel in cultured neonatal rat ventricular myocytes (18). Most studies regarding the electrophysiological alterations associated with cardiac hypertrophy were performed on the pressure-overload model, which has been associated with reduction in I to (6,15,16,53) and no change (6,57) or a decrease in I K (13,14,29,30) and I K1 (5,15,37). Interestingly, Brooksby et al (5) have shown that the electrical remodeling related to cardiac hypertrophy was restricted to a decrease in I K1 current density with no difference in the resting potential level of cardiomyocytes from control and spontaneously hypertensive rats.…”
mentioning
confidence: 99%